Tubos de impedância e suas aplicações na determinação de propriedades acústicas de meios porosos - Stross, Antonio Carlos Távora (1975)
Acoustic impedances and absortion coefficients in fluid-saturated porous solids are experimentally determined in air and water in impedance tubes. An experimental methodology is developed for the measurements in water. A study is made of the ways in which the experimentally measured parameters porosity, density, permeability and sample thickness, influence acoustic impedance and absortion. Those parameters are introduced into an existent theory of propagation in porous media and the resulting absortion is compared with the one obtained experimentally. The higher values of the measured acoustic absortion as compared to the ones predicted by the theory are atributed to resonancess in the cavities of the porous esqueleton.